Change over time in adolescent smoking, cannabis use and their association: findings from the School Health Research Network in Wales. (29th September 2020) - Page, N; Hallingberg, B; Brown, R; Lowthian, E; Hewitt, G; Murphy, S; Moore, G
Abstract: Background: While tobacco smoking has declined among UK youth in recent decades, cannabis use has begun to show some growth. Given their interrelationship, growth in cannabis use may act as a barrier to continued reduction in youth smoking. This paper assesses recent tobacco and cannabis use trends in Wales, and their association, to explore whether change in cannabis use might have impacted youth tobacco smoking prevalence. Methods: Repeat cross-sectional data on tobacco and cannabis use were obtained from biennial Welsh Student Health and Wellbeing surveys between 2013 and 2019. Data were pooled and analysed using logistic regression with adjustment for school-level clustering. Results: No change in regular youth tobacco smoking was observed between 2013 and 2019. In contrast, current cannabis use increased during this time, and cannabis users had significantly greater odds of regular tobacco smoking. After adjusting for change in cannabis use, a significant decline in youth tobacco smoking was observed (OR 0.95; 95% confidence intervals: 0.92, 0.97). Conclusion: Recent growth in cannabis use among young people in Wales may have offset prospective declines in regular tobacco smoking. Further reductions in youth smoking may require more integrated policy approaches to address the co-use of tobacco and cannabis among adolescents.